Penerapan strategi pembelajaran schema based instruction untuk meningkatkan keterampilan pemecahan masalah bangun datar pada peserta didik kelas III sekolah dasar - Muhammad Syarif Hidayatussalam; Hadi Mulyono; Riyadi Riyadi (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
The purpose of research is improve problem solving skills in the stories matter of solid geometry by applying the Schema Based Istruction (SBI) learning strategy. This research is Classroom Action Research with two cycles. The subjects of this research were students of IIID class at SD Djama’atul Ichwan in the 2018/2019 academic year, consists of 31 students. This research uses data collection techniques in the form of interviews, observations, tests, and documentation with data analysis of source triangulation, technique triangulation, and content validity. The analysis of the data used is the interactive analysis model of Miles-Huberman. The results showed that the implementation of the Schema Based Instruction (SBI) learning strategy can improve problem solving skills of flat-waking story questions for students of class IIID SD Djama'atul Ichwan in the 2018/2019 academic year. This is evidenced by the increase in the percentage of problem solving skills that have met the research target by 80%. The data obtained from the first cycle with the percentage of the first meeting was 55% classical, the second meeting was 35% classical, and the third meeting was 87% classical. The research was continued with the second cycle with a percentage of 81%, the second learning was 84%, and the third learning was 94% classically.